Modulation of Small-Intestine Morphology in Mice by a Novel Supplement Containing Silybum marianum, Yeast β-Glucan, Prebiotics, and Minerals - Nucci, Ricardo Aparecido Baptista; Nehmi-Filho, Victor Abou; Bastos, Marta Ferreira; de Freitas, Jéssica Alves; Otoch, José Pinhata; Pessoa, Ana Flávia Marçal; Jacob-Filho, Wilson (Journal of Health and Allied Sciences NU, 2023)
Silymarin, derived from Silybum marianum, has recently demonstrated its potential to improve health in conditions such as obesity and metabolic disturbances. Understanding the impact of nutraceuticals on intestinal morphology is crucial for developing supplements that promote a higher quality of life. Therefore, this study aimed to investigate the effects of nutraceutical supplementation with silymarin on the morphology of the small intestine. Sixty-day-old adult male C57BL/6 mice were divided into two groups: one receiving a standard chow (control) and the other receiving a novel silymarin supplement (experimental). Following the experimental period, the animals were euthanized, and fragments of the small intestine were collected for histochemical analysis using Masson's trichrome and periodic acid-Schiff with Alcian blue staining techniques. Our results revealed an increase in the number of villi per analyzed field in the experimental group, accompanied by a decrease in basic mucin, crypt depth, mucosal thickness, and villus spacing. In conclusion, this novel nutraceutical supplementation may play a crucial role in modulating small intestine morphology and enhancing absorption capacity.
Keywords: intestine; mice; morphology; Silymarin; supplementation